Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

New Algebra Set!!! [#permalink]
18 Mar 2013, 06:56

27

This post received KUDOS

Expert's post

23

This post was BOOKMARKED

The next set of medium/hard PS algebra questions. I'll post OA's with detailed explanations after some discussion. Please, post your solutions along with the answers.

1. If x=\sqrt[4]{x^3+6x^2}, then the sum of all possible solutions for x is:

Re: New Algebra Set!!! [#permalink]
22 May 2013, 21:19

Bunuel wrote:

[ Take the given expression to the 4th power: x^4=x^3+6x^2;

Re-arrange and factor out x^2: x^2(x^2-x-6)=0;

Factorize: x^2(x-3)(x+2)=0;

So, the roots are x=0, x=3 and x=-2. But x cannot be negative as it equals to the even (4th) root of some expression (\sqrt{expression}\geq{0}), thus only two solution are valid x=0 and x=3.

The sum of all possible solutions for x is 0+3=3.

Answer: D.

Hi Bunuel, Request you to please let me know where I'm making a mistake.

Since x^3+6*x^2 >= 0 Then, x^2(x+6)>=0

i.e (x-0)^2(x-(-6))>=0 This implies thatx>=-6 Hence, x=-2 is a valid root, and sum of all roots should bex=3+(-2) = 1 Please let me know where I am going wrong.

Re: New Algebra Set!!! [#permalink]
23 May 2013, 01:00

Expert's post

imhimanshu wrote:

Bunuel wrote:

[ Take the given expression to the 4th power: x^4=x^3+6x^2;

Re-arrange and factor out x^2: x^2(x^2-x-6)=0;

Factorize: x^2(x-3)(x+2)=0;

So, the roots are x=0, x=3 and x=-2. But x cannot be negative as it equals to the even (4th) root of some expression (\sqrt{expression}\geq{0}), thus only two solution are valid x=0 and x=3.

The sum of all possible solutions for x is 0+3=3.

Answer: D.

Hi Bunuel, Request you to please let me know where I'm making a mistake.

Since x^3+6*x^2 >= 0 Then, x^2(x+6)>=0

i.e (x-0)^2(x-(-6))>=0 This implies thatx>=-6 Hence, x=-2 is a valid root, and sum of all roots should bex=3+(-2) = 1 Please let me know where I am going wrong.

Thanks

Plug x=-2 into x=\sqrt[4]{x^3+6x^2}. Does the equation hold true? _________________

Re: New Algebra Set!!! [#permalink]
23 May 2013, 04:03

2. The equation x^2 + ax - b = 0 has equal roots, and one of the roots of the equation x^2 + ax + 15 = 0 is 3. What is the value of b?

A. -64 B. -16 C. -15 D. -1/16 E. -1/64

Solution:

x^2 + ax + 15 = 0 equation has one root as 3. only possible values of getting product of the roots 15 , having one root 3 is 5*3. x^2-5x-3x+15=0 take common values out => x(x-5)-3(x-5) =0 => x=5 and x=3(what was given) , from this we get a= -8.

x^2 -8x - b =0 => if roots are equal then b^2-4ac=0, 64+4b=0 from this b=-16

Re: New Algebra Set!!! [#permalink]
23 Jun 2013, 00:37

Expert's post

aquax wrote:

Hi,

For the first question, what do you mean by "But X cannot be negative as it equals to the even (4th) root of some expression"?

x cannot be negative as it equals to the even (4th) root of some expression (\sqrt[even]{expression}\geq{0}), thus only two solution are valid x=0 and x=3.

When the GMAT provides the square root sign for an even root, such as \sqrt{x} or \sqrt[4]{x}, then the only accepted answer is the positive root. That is, \sqrt{25}=5, NOT +5 or -5. Even roots have only non-negative value on the GMAT.

In contrast, the equation x^2=25 has TWO solutions, \sqrt{25}=+5 and -\sqrt{25}=-5.

So, we need to maximize the value of -3(x-2)^2-2(y+3)^2-9.

Since, the maximum value of -3(x-2)^2 and -2(y+3)^2 is zero, then the maximum value of the whole expression is 0+0-9=-9.

Answer: B.

Hi Bunuel,

Just as a matter of fact can you please explain that how you reached to factorization. In other words how a candidate will decide how to split -39 between (X,Y).

Your reply is appreciated !!

Rgds, TGC !! _________________

Rgds, TGC! _____________________________________________________________________ I Assisted You => KUDOS Please _____________________________________________________________________________

Re: New Algebra Set!!! [#permalink]
24 Oct 2013, 00:01

Expert's post

NeetiGupta wrote:

Bunuel wrote:

Bunuel wrote:

Take the given expression to the 4th power: x^4=x^3+6x^2;

Re-arrange and factor out x^2: x^2(x^2-x-6)=0;

Factorize: x^2(x-3)(x+2)=0;

So, the roots are x=0, x=3 and x=-2. But x cannot be negative as it equals to the even (4th) root of some expression (\sqrt{expression}\geq{0}), thus only two solution are valid x=0 and x=3.

The sum of all possible solutions for x is 0+3=3.

Answer: D.

Hi Bunuel, Request you to please let me know where I'm making a mistake.

Since x^3+6*x^2 >= 0 Then, x^2(x+6)>=0

i.e (x-0)^2(x-(-6))>=0 This implies thatx>=-6 Hence, x=-2 is a valid root, and sum of all roots should bex=3+(-2) = 1 Please let me know where I am going wrong.

Thanks

Plug x=-2 into x=\sqrt[4]{x^3+6x^2}. Does the equation hold true?

Hi Brunel if say x=16. x^1/2 has two values +4 & -4. So why x^1/4 cannot have +2 & -2 as as values ? Please explain

First of all it's 4th root not 2nd root. Next, \sqrt[4]{16}=2, not +2 or -2.

When the GMAT provides the square root sign for an even root, such as \sqrt{x} or \sqrt[4]{x}, then the only accepted answer is the positive root. That is, \sqrt{25}=5, NOT +5 or -5.

In contrast, the equation x^2=25 has TWO solutions, +5 and -5. Even roots have only non-negative value on the GMAT.

Re: New Algebra Set!!! [#permalink]
05 Apr 2014, 02:42

Q1. Option D. Raising both LHS and RHS to fourth power,and making RHS=0 we get x^4-x^3-6x^2=0 Taking x^2 common and factorizing, x^2(x+2)(x-3)=0 Three possible values of x are -2,3 and 0 But x can't be -ve. So sum of possible values=3